2014
DOI: 10.1371/journal.pone.0095207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Cover on Fitness and Behavioural Traits of Captive Red-Eyed Tree Frogs (Agalychnis callidryas)

Abstract: Despite the importance of ex situ conservation programmes as highlighted in the Amphibian Conservation Action Plan, there are few empirical studies that examine the influence of captive conditions on the fitness of amphibians, even for basic components of enclosure design such as cover provision. Maintaining the fitness of captive amphibian populations is essential to the success of ex situ conservation projects. Here we examined the impact of plant cover on measures of fitness and behaviour in captive red-eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…Some of these bacteria can confer resistance to infection from Batrachochytrium dendrobatidis (Harris et al 2006, 2009a,b, Lam et al 2010, an emerging fungal pathogen influencing global declines in amphibian populations (Daszak et al 2003, Wake & Vredenburg 2008. Current evidence indicates that the amphibian skin bacteria can be acquired and maintained via horizontal (host-to-host e.g., Rebollar et al 2016a), environmental (e.g., Michaels et al 2014, Loudon et al 2016, Rebollar et al 2016a, and/or vertical transmission (from parent to offspring, e.g., Banning et al 2008, Walke et al 2011. Vertical transmission of bacterial symbionts has been suggested to occur in two amphibian species with parental care based on the presence of similar bacteria on parents and their eggs: a salamander with maternal care, Hemidactylium scutatum (Banning et al 2008), and a frog with paternal care, Hyalinobactrachium colymbiphyllum (Walke et al 2011).…”
mentioning
confidence: 99%
“…Some of these bacteria can confer resistance to infection from Batrachochytrium dendrobatidis (Harris et al 2006, 2009a,b, Lam et al 2010, an emerging fungal pathogen influencing global declines in amphibian populations (Daszak et al 2003, Wake & Vredenburg 2008. Current evidence indicates that the amphibian skin bacteria can be acquired and maintained via horizontal (host-to-host e.g., Rebollar et al 2016a), environmental (e.g., Michaels et al 2014, Loudon et al 2016, Rebollar et al 2016a, and/or vertical transmission (from parent to offspring, e.g., Banning et al 2008, Walke et al 2011. Vertical transmission of bacterial symbionts has been suggested to occur in two amphibian species with parental care based on the presence of similar bacteria on parents and their eggs: a salamander with maternal care, Hemidactylium scutatum (Banning et al 2008), and a frog with paternal care, Hyalinobactrachium colymbiphyllum (Walke et al 2011).…”
mentioning
confidence: 99%
“…Several studies have reported changes in the microbial associated communities when animals are moved from the wild to captive environments ( Isaacs et al, 2009 ; Dhanasiri et al, 2011 ; Wienemann et al, 2011 ; Nelson et al, 2013 ). In amphibians, research assessing the effect of captivity on bacterial communities is increasing ( Antwis et al, 2014 ; Becker et al, 2014 ; Michaels, Antwis & Preziosi, 2014 ; Kueneman et al, 2016 ). Through culture-independent and dependent approaches, these studies have demonstrated changes in the skin bacterial community composition due to conditions imposed by captivity.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have suggested that skin associated microbes of individuals in captivity differ from those in the wild ( Becker et al, 2014 ; Kueneman et al, 2016 ; Sabino-Pinto et al, 2016 ). In the case of the red-eyed tree frog ( Agalychnis callidryas ) , community composition, species richness, and abundance of bacterial groups seem to be influenced mainly by the availability of carotenoids in their diet ( Antwis et al, 2014 ), and by the cover provided in the enclosures ( Michaels, Antwis & Preziosi, 2014 ). However, other factors including humidity, temperature, pH and disinfection methods affect the presence of certain bacterial species and could facilitate or impede colonization and establishment in the host skin ( Mendoza et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotenoid availability also affects the composition of bacterial colonies associated with amphibian skin (Antwis et al 2014). Diverse bacterial colonies may offer protection against pathogens (Antwis et al 2014), but captive environments can significantly alter the bacterial skin floras implicated in disease resistance (Loudon et al 2013;Antwis et al 2014;Michaels et al 2014d); captive bred animals may therefore lack this protection.…”
Section: Easy To Maintain and Breedmentioning
confidence: 99%